The role of FAS gene variants in inflammatory bowel disease - Ayhan Demir; Resul Kahraman; Gonca Candan; Arzu Ergen (Turkish Journal of Gastroenterology, 2020)
Background/Aims: The analysis of genes thought to be important in inflammatory bowel disease (IBD) has shown that more than half of IBD-related genes are also associated with other autoimmune diseases. The aim of this study was to detect a possible association between the polymorphisms of the (−670 A/G, −1377 G/A) fFas cell surface death receptor (FAS) gene promoter and susceptibility to IBD in the Turkish population.Materials and Methods: In total, 125 patients with IBD, including 73 ulcerative colitis and 52 Crohn’s disease and also 101 healthy controls without any pathological signs of IBD were considered for the study. Real-time polymerase chain reaction technique was used to detect FAS polymorphisms in this study.Results: The analysis of FAS −670 A/G polymorphism indicated that the frequency of GG genotype was significantly increased in patients compared with controls (p<0.001). Additionally, AG genotype (p<0.001) and A allele (p<0.001) frequencies were higher in controls than in patients. The analysis of FAS −1377 G/A polymorphism revealed that the frequency of AA genotype was meaningfully increased in patients compared with controls (p<0.001). Additionally, GG genotype (p<0.001) and G allele (p<0.001) frequencies were increased in controls when compared with patients.Conclusion: FAS −670A/G GG genotype seemed to be a protective allele against IBD; however, AA genotype and A allele were associated with elevated risk of IBD. In the FAS −1377G/A polymorphism, frequencies of the G allele and GG genotype were observed to be protective against IBD, whereas AA, GA genotypes, and A allele frequency increased in the patient group.Cite this article as: Demir A, Kahraman R, Candan G, Ergen A. The role of FAS gene variants in inflammatory bowel disease. Turk J Gastroenterol 2020; 5: 356-61.